Application and development of Organ-on-a-Chip technology in cancer therapy - Wang, Ling xiao; Liu, Shu ling; Wu, Ning (Frontiers in Oncology, 2025)
Cancer therapies are limited by tumor heterogeneity, complex tumor microenvironments (TME), and treatment resistance. Traditional 2D cell cultures cannot replicate tumor 3D architecture and dynamic interactions, reducing clinical relevance. Organoid-on-a-Chip (OoC) technology overcomes these gaps by integrating microfluidics, tissue engineering, and cell biology to create physiologically accurate 3D models. This platform simulates TME dynamics—including vascularization and multi-organ interactions—surpassing static conventional models. Key advancements: (1) Three development phases: basic 3D culture (2009–2015), multi-organ coupling (2016–2020), and clinical translation (2021–present); (2) FDA Modernization Act 2.0 (2022) enabling OoC data as sole preclinical evidence for clinical trials; (3) Patient-derived organoids (PDOs) retaining parental tumors’ features with >87% drug-response accuracy in colorectal cancer. Vascularized tumor chips further study angiogenic dynamics and drug efficacy. While OoC excels in drug screening, toxicity testing, and personalized oncology, challenges persist in simulating systemic immune responses. Advancing multi-organ integration and policy alignment remains critical to replace animal models and advance precision cancer therapy.